The Effectiveness of the Repetition Learning Method (Drill Method) in Improving Basic Functional Literacy Skills in Students at Sd Wara, Sd Manelek, and Sd Sikhem Bariat in 3t Areas - Ida Siti Hamidah; Zulfah Riska Purnama; Hermin Hermin; Nurlaely Nurlaely; Syahrir Syahrir (Eduvest - Journal of Universal Studies, 2026)
This research aims to determine the effectiveness of the learning method by means of repetition (drill method) in improving basic functional literacy skills (reading, writing, and arithmetic) in students in three elementary schools (SD), namely SD Wara, SD Manelek, and SD Sikhem Bariat. This study used qualitative research where participants consisted of 125 students who had sub-average literacy skills. The research was carried out through drill method training for 30 days of meetings with materials focused on vocabulary, simple sentences, and numeracy in the context of the daily lives of elementary school students. Data were collected through functional literacy ability tests before (pretest) and after (posttest) the intervention, as well as participatory observation. The results showed that 85% of students experienced an increase in reading speed and fluency, 80% of students showed improvement in writing simple sentences with better spelling, and 82% of students were able to complete basic arithmetic operations without the help of fingers. Overall, 80% of students (90 out of 171 students) experienced a significant improvement in basic functional literacy skills after participating in the drill method training for 30 days. In this case, it can be concluded that the drill method has proven effective in improving the basic functional literacy skills of elementary school students in the 3T Area. This method can be used as a practical and applicable alternative learning model to overcome difficulties in learning literacy in areas with limited resources and access.